(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2023)
For assessments of hand function, it is crucial, mostly in the medical field, to record hand motions. For testing manual dexterity and rehabilitation, many data gloves have indeed been created. Regarding the sensor technique used, evaluation methodologies, and reasons, this article review intends to study and assess the features of technology-assisted hand evaluations and their uses. This study seeks to facilitate the design and translation of technology-aided hand functional assessment to clinical practice in accordance with the inadequacies of present applications and current alternatives afforded by upcoming methods. A number of previous studies (from 2012 to 2021) were relied upon to conduct a research study of the most important techniques used in analyzing and evaluating hand movement. The sensing technologies that are most frequently employed for kinematic and kinetic analysis are force sensing resistors (FSR) and inertial measurement units (IMU).